Angular velocity affects trunk muscle strength and EMG activation during isokinetic axial rotation - Fan, J.-Z.; Liu, X.; Ni, G.-X. (BioMed Research International, 2014)
OBJECTIVE To evaluate trunk muscle strength and EMG activation during isokinetic axial rotation at different angular velocities. METHOD Twenty-four healthy young men performed isokinetic axial rotation in right and left directions at 30, 60, and 120 degrees per second angular velocity. Simultaneously, surface EMG was recorded on external oblique (EO), internal oblique (IO), and latissimus dorsi (LD) bilaterally. RESULTS In each direction, with the increase of angular velocity, peak torque decreased, whereas peak power increased. During isokinetic axial rotation, contralateral EO as well as ipsilateral IO and LD acted as primary agonists, whereas, ipsilateral EO as well as contralateral IO and LD acted as primary antagonistic muscles. For each primary agonist, the root mean square values decreased with the increase of angular velocity. Antagonist coactiviation was observed at each velocity; however, it appears to be higher with the increase of angular velocity. CONCLUSION Our results suggest that velocity of rotation has great impact on the axial rotation torque and EMG activity. An inverse relationship of angular velocity was suggested with the axial rotation torque as well as root mean square value of individual trunk muscle. In addition, higher velocity is associated with higher coactivation of antagonist, leading to a decrease in torque with the increase of velocity.